Lectotypification of Geranium grevilleanum Wall. (Geraniaceae) - Wagh, Vijay V.; Hurrah, Imtiyaz Ahmad (Phytotaxa, 2019)
During studies of Geranium in India, it was found that no lectotype had been designated for Geranium grevilleanum. Although several researchers studied this species, they provide only the collection number, type locality and herbarium where it is housed but failed to mention which sheet should be regarded as a type specimen. Therefore, the original material of that species is here established and a lectotype is selected.